Strategies for integrated health care provision oriented at tuberculosis patients and other socially important lung diseases - K. M. Yavorskiy; S. M. Аleksandru; V. V. Vilk; V. A. Bolotnikova; A. F. Moskovchuk; A. G. Brumaru; I. V. Shinkarenko (Туберкулез и болезни лёгких)
.